2003
DOI: 10.1215/s0012-7094-03-11614-2
|View full text |Cite
|
Sign up to set email alerts
|

Tableau atoms and a new Macdonald positivity conjecture

Abstract: Let Λ be the space of symmetric functions and V k be the subspace spanned by the modified Schur functions {S λ [X/(1 − t)]} λ1≤k . We introduce a new family of symmetric polynomials, {A, constructed from sums of tableaux using the charge statistic. We conjecture that the polynomials A (k) λ [X; t] form a basis for V k and that the Macdonald polynomials indexed by partitions whose first part is not larger than k expand positively in terms of our polynomials. A proof of this conjecture would not only imply the M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
132
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(136 citation statements)
references
References 18 publications
2
132
0
1
Order By: Relevance
“…Having discarded determinants, symmetry, commutativity does not suffice to cover all the generalizations of Schur functions, for example the Macdonald polynomials or the k-Schur functions [14].…”
Section: Extensionsmentioning
confidence: 99%
“…Having discarded determinants, symmetry, commutativity does not suffice to cover all the generalizations of Schur functions, for example the Macdonald polynomials or the k-Schur functions [14].…”
Section: Extensionsmentioning
confidence: 99%
“…, h k ]. The k-Schur functions were introduced by Lascoux, Lapointe and Morse [11] as a basis of Λ (k) . It was established by Lam [7] that their corresponding constant structures (called k-Littlewood-Richardson coefficients) are nonnegative.…”
Section: Introductionmentioning
confidence: 99%
“…In one such study [92], Lapointe, Lascoux, and Morse found computational evidence for a family of new bases for subspaces Λ t k in a filtration Λ t…”
Section: Introductionmentioning
confidence: 99%
“…They were first defined as a sum of the usual Schur functions over a combinatorially defined collection of tableaux known as a k-atom. Lapointe, Lascoux, and Morse [92] conjectured that the Macdonald symmetric functions expand positively in terms of k-Schur functions. An obvious difficulty with this approach is a missing algebraic connection that could be used to connect Macdonald symmetric functions with the combinatorics of k-atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation